SISTEM INFORMASI EKSPOR DAN IMPOR BERBASIS WEB PADA PT PULAU MAS MORO MULIA - Liu, Agustian; Amrizal (LPPM Universitas Putera Batam, 2024)
The development of information technology has had a significant influence on various areas of life. As time goes by, the development of new and sophisticated technology continues to occur, one of which is efforts to increase the efficiency of product distribution so that it can reach customers more quickly. PT Pulau Mas Moro Mulia is a company engaged in the distribution and trade of goods across countries. However, PT Pulau Mas Moro has not felt the benefits of technology because it still uses a manual system. PT Pulau Mas Moro is experiencing problems in terms of document management because it does not have adequate information technology to update documents. This has an impact on companies, such as frequent loss of imported goods due to discrepancies in data from the goods sent to their destination, causing losses for the company. To avoid this incident, a system is needed that is able to control the accuracy of documents for imported goods. Systems designed using the prototype method can be web-based export and import systems. The results of this research succeeded in designing an information system that combines the company's business needs with modern web design principles.